BIBLIOMETRIC ANALYSIS: THE EFFECT OF STEM-BASED PJBL AND E-LEARNING MODELS ON STUDENT LEARNING MOTIVATION IN ELEMENTARY SCHOOL - Turrahmah, Alifa; Hasibuan, Qonithatu Namora; Azizah, Sarah Nur (Journal of Physical Education, Health and Sports Recreation, 2025)
This study aims to analyze the influence of the STEM-based Project-Based Learning (PJBL) model and e-learning on elementary school students' learning motivation through a bibliometric approach. The method used was bibliometric analysis with the help of VOSviewer software to map research trends based on publication data from the Crossreff database. The analysis revealed six main keyword clusters: PJBL integration in STEM, technology and e-learning, motivation and engagement, evaluation of learning outcomes, the role of teachers and curriculum, and implementation challenges. These findings demonstrate that the global research focus is shifting toward active learning supported by digital technology and centered on students. In conclusion, the STEM-based PJBL approach integrated with e-learning contributes positively to increasing student learning motivation. It is recommended that teacher training and digital infrastructure support be improved to maximize the effectiveness of implementation at the elementary school level.